Efektivitas Penyuluhan Metode Aplikasi Inovatif GIGI SEHAT dan Pertunjukan Panggung Boneka terhadap Pengetahuan Kesehatan Gigi dan Mulut Siswa Kelas IV & V SDN Kebonsari 02 Jember (The Effectiveness Counseling of Innovative Application GIGI SEHAT Method and Puppet Show to Dental Health Knowledge for IV & V Grade Students of SDN Kebonsari 02 Jember) - Qatrunnada Fath; Hestieyonini Hadnyanawat; Kiswaluyo . (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Background: UKGS of Public Health Office in 2009 shows much the elementary school children are treated in Community Health Center because of teeth decay in the amount of 41,38%. Counseling in UKGS all this time uses lecture method which needs dentists, times, and energy in implementation. In fact human resources to do the UKGS are inadequate, so need an alternative method which is suited. Objective: To know the effectiveness of counseling with innovative application GIGI SEHAT and puppet show to dental health knowledge for IV & V grade students of SDN Kebonsari 02 Jember. Method: The subject were students in IV and V grade of SDN Kebonsari 02 Jember. Students are divided into three groups counseling method, there were innovative application GIGI SEHAT, puppet show and lecture. Research procedure was divided into three stages which were pretest, counseling, and post test. Results and Conclusions: The data before and after counseling all of the methods were analysed with Paired t-test, and the result of application GIGI SEHAT and lecture showed that were significant difference (p<0,05) and the puppet show was not significant. The results of three different test methods used One Way Anova Test showed there was the significant difference between three method (p>0,05). The different test counseling effectiveness of each methods performed further test used Independent T-test showed that application GIGI SEHAT and puppet show, application GIGI SEHAT and lectures there were the significant differences ( p< 0.05 ). Keywords: Dental Health Counseling, Innovative Applications GIGI SEHAT, Lecture, Puppet Show, UKGS